1990
DOI: 10.1002/1097-4679(199009)46:5<565::aid-jclp2270460504>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Intense personal experiences: Subjective effects, interpretations, and after-effects

Abstract: Following leads by Maslow (1964, 1968) and others who described peak experiences, this study was designed to learn more about the (1) subjective effects; (2) after‐effects; and (3) interpretations of intense positive and negative experiences. Comparisons were made between respondents' “most positive” and “most negative” experiences and between these positive experiences and those of members of a yoga ashram. It was found that except for the differences in affect, positive and negative experiences were similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Ashram respondents showed a higher percentage of positive responses on a number of indices, including “Felt a personality change,” “Experience resulted in change in life,” “Experience of oneness,” and “In touch with divine or spiritual” [13]. These data would support the notion that yoga practice may enhance transformational processes, including spiritual, transcendent states.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Ashram respondents showed a higher percentage of positive responses on a number of indices, including “Felt a personality change,” “Experience resulted in change in life,” “Experience of oneness,” and “In touch with divine or spiritual” [13]. These data would support the notion that yoga practice may enhance transformational processes, including spiritual, transcendent states.…”
Section: Introductionmentioning
confidence: 89%
“…A study of members of a yoga ashram revealed that they showed statistically greater psychological characteristics of state of consciousness, and after-effects and interpretation of positive life experiences than those experienced by a control group of non-ashram residents [13]. Ashram respondents showed a higher percentage of positive responses on a number of indices, including “Felt a personality change,” “Experience resulted in change in life,” “Experience of oneness,” and “In touch with divine or spiritual” [13].…”
Section: Introductionmentioning
confidence: 99%
“…personal crises; hence, negative stressors can produce positive change [Cordova et al, 2001;Wilson and Spencer, 1990]. Positive stressors can bring about positive change as well, especially when the positive experience is deliberately sought out.…”
Section: Behavioral Health and Salutogenesismentioning
confidence: 99%
“…The lessening of negative affectivity, as reported in the literature (Christopher et al, 2002;Wilson and Spencer, 1990) is clearly an aspect of the peak phenomenon; this effect appears evident in the data collected for this study.…”
Section: Open To Themsupporting
confidence: 83%
“…reported greater feelings of self confidence, self acceptance, self worth, and self regard, a marked increase in autonomy and authenticity, and an increased appreciation and need for solitude" (p.606). Wilson and Spencer (1990), examine the relationship between intense personal experiences (peak experiences), and positive personal growth, in their psychology based work.…”
Section: The Benefits Of Peak Experiencesmentioning
confidence: 99%